The Effect Of Good Corporate Governance And Political Connection On Value Firm - Agus Bandiyono (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
This study aims to determine the effect of applying good corporate governance and political connections to firm value. The data of this study are secondary data of manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. Data were analyzed using panel data estimation. The results of this study indicate that partial corporate governance has a positive and significant effect on firm value, political connection variables have a positive and significant effect on firm value and together corporate governance and political connections have a positive and significant effect on firm value.